2011
DOI: 10.1155/2011/276769
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Auricular Transcutaneous Electrical Nerve Stimulation for Managing Posthysterectomy Pain

Abstract: Background. A patient- and assessor-blinded randomized controlled trial was conducted to examine the effectiveness of auricular transcutaneous electrical nerve stimulation (TENS) in relieving posthysterectomy pain. Method. Forty-eight women who had undergone a total abdominal hysterectomy were randomly assigned into three groups (n = 16 each) to receive either (i) auricular TENS to therapeutic points (the true TENS group), (ii) auricular TENS to inappropriate points (the sham TENS group), or (iii) 20 minutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 52 publications
1
17
0
3
Order By: Relevance
“…A total of 121 full-text articles were reviewed. After application of the inclusion criteria, 59 RCTs [ 3 , 6 , 14 , 19 , 20 , 23 25 , 28 – 78 ] conducted between 1986 and 2014 were included in the review ( Figure 1 ; Tables 2 – 4 ). Nine publications were in Chinese, and the remaining 50 publications were in English.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 121 full-text articles were reviewed. After application of the inclusion criteria, 59 RCTs [ 3 , 6 , 14 , 19 , 20 , 23 25 , 28 – 78 ] conducted between 1986 and 2014 were included in the review ( Figure 1 ; Tables 2 – 4 ). Nine publications were in Chinese, and the remaining 50 publications were in English.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen [ 6 , 19 , 24 , 62 – 72 ] RCTs used auricular points for stimulation. Data synthesis from 12 studies showed significantly lower VAS scores in intervention groups than in all types of control group ( P = 0.001), and similar results were obtained in comparison with standard treatment ( P = 0.04) and sham/placebo control ( P = 0.02) groups ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative Nausea and Vomiting (PONV) occurs in up to 30% of unselected surgical patients and is the most frequent side effect after anaesthesia [1][2][3]. PONV not only reduced patient satisfaction but also was rated worse than postoperative pain in some of the patients [4,5].…”
Section: Introductionmentioning
confidence: 99%